Implementasi Supervisi Akademik Berbasis Coaching oleh Kepala Sekolah dalam Meningkatkan Kompetensi Pedagogik Guru Sekolah Dasar Negeri Cicalengka 06 Kabupaten Bandung - Suharyanto H. Soro; Arif Rahman Hakim; Sri Rahayu; Witi Restuning Pangestuti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research is based on teachers' teaching abilities and pedagogical abilities which are still low. This research aims to obtain an overview of the implementation of coaching-based academic supervision in improving teacher pedagogical competence. Against the background of efforts to increase teacher competency by means of coaching-based academic supervision. This research focuses on how to plan, implement and obstacles in coaching-based academic supervision. The coaching-based supervision process uses the TIRTA flow. TIRTA is a coaching model which is an acronym for Goals, Identification, Action Plans and Responsibilities. This research uses descriptive research, data collected through coaching interviews between school principals and teachers, observation by directly observing the academic supervision process and documentation. The researchers' findings in the field after carrying out academic supervision using coaching techniques experienced an increase in the quality of learning based on qualitative findings in the quality of learning. Qualitative findings from interviews also reveal that coaching techniques in academic supervision play a role in providing convenience and helping school principals and teachers develop their potential optimally.